2001
DOI: 10.1046/j.1365-2621.2001.00426.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the method of drying on the colour of dehydrated products

Abstract: Summary We tested the hypothesis that an optimum method of drying fruit could be designed. The effect of the method used for drying on colour of apple, banana, potato and carrot was investigated for five different methods of drying: conventional, vacuum, microwave, freeze and osmotic drying. Colour characteristics were studied by measuring lightness (L), redness (a) and yellowness (b) using a Hunter Lab chromatometer. The method used to dry the material was found to significantly affect the three colour parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
117
0
11

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(138 citation statements)
references
References 11 publications
10
117
0
11
Order By: Relevance
“…Variety Roslin Eburu had the highest colour score (5.68) while Cangi had the lowest score (2.73). Colour is one of the most critical sensory properties that determines acceptability of a food (Surkan et al, 2009) and hence must conform to consumer requirement (Krokida et al, 2001). Since there was a high correlation (r=-0.92) between PC/SFA and sensory colour scores for potato crisps processed from the 24 cultivars, it therefore means that the panelists scores were in agreement with the objective colour measurement (Table 5).…”
Section: Resultsmentioning
confidence: 84%
“…Variety Roslin Eburu had the highest colour score (5.68) while Cangi had the lowest score (2.73). Colour is one of the most critical sensory properties that determines acceptability of a food (Surkan et al, 2009) and hence must conform to consumer requirement (Krokida et al, 2001). Since there was a high correlation (r=-0.92) between PC/SFA and sensory colour scores for potato crisps processed from the 24 cultivars, it therefore means that the panelists scores were in agreement with the objective colour measurement (Table 5).…”
Section: Resultsmentioning
confidence: 84%
“…The method of drying and process conditions also infl uence the texture of dried products. Krokida et al (2001) studied the quality of apple, banana, potato and carrot with different drying methods such as convective, vacuum, microwave, freeze and osmotic drying. It was found that air, vacuum and microwave dried materials caused extensive browning in fruits and vegetables whereas freeze drying seemed to preserve colour changes, resulting a produce with improved colour characteristics.…”
Section: Physical Qualitymentioning
confidence: 99%
“…One way to preserve such plant products is to dry them in order to preserve their desirable qualities, reduce storage volume and to extend shelf-life. In addition, it is also important to retain the biological activity of important phytoconstituents, including antioxidants and nutrients as well as avoid undesirable chemical or physical changes like browning and loss of colour (Korkida et al 2001). Therefore, the selection of proper drying conditions is of prime importance to minimize nutrient loss and quality deterioation during dehydration.…”
Section: Introductionmentioning
confidence: 99%